2018
DOI: 10.1128/jvi.02050-17
|View full text |Cite
|
Sign up to set email alerts
|

RNA Binding Protein RBM38 Regulates Expression of the 11-Kilodalton Protein of Parvovirus B19, Which Facilitates Viral DNA Replication

Abstract: Human parvovirus B19 (B19V) expresses a single precursor mRNA (pre-mRNA), which undergoes alternative splicing and alternative polyadenylation to generate 12 viral mRNA transcripts that encode two structural proteins (VP1 and VP2) and three nonstructural proteins (NS1, 7.5-kDa protein, and 11-kDa protein). Splicing at the second 5' donor site (D2 site) of the B19V pre-mRNA is essential for the expression of VP2 and the 11-kDa protein. We previously identified that -acting intronic splicing enhancer 2 (ISE2) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 57 publications
(99 reference statements)
0
31
0
Order By: Relevance
“…Identification of B19V ISE2-interacting proteins. We previously reported that ISE2 is critical for the recognition of the D2 site for splicing and that the interaction of RBM38 with ISE2 promotes splicing of the intron from the D2 to the A2-2 splice sites (37,41). Thus, we asked whether other host factors could interact with ISE2 and facilitate the alternative splicing at these sites.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Identification of B19V ISE2-interacting proteins. We previously reported that ISE2 is critical for the recognition of the D2 site for splicing and that the interaction of RBM38 with ISE2 promotes splicing of the intron from the D2 to the A2-2 splice sites (37,41). Thus, we asked whether other host factors could interact with ISE2 and facilitate the alternative splicing at these sites.…”
Section: Resultsmentioning
confidence: 99%
“…The viral precursor mRNA (pre-mRNA) is alternatively spliced and alternatively polyadenylated resulting in the generation of nine major viral mRNA transcripts that encode capsid proteins (VP1 and VP2) and nonstructural proteins (NS1, 11-kDa, and 7.5-kDa) (31)(32)(33)(34). NS1 is the only viral protein that is essential for B19V DNA replication (35)(36)(37). However, the small nonstructural protein 11-kDa, which is localized predominantly in the cytoplasm and plays an enhancement role in viral DNA replication, is unique among parvoviruses (38).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It may also infect non-erythroid lineage cells such as myocardial endothelial cells [60]. The tropism of B19V for EPCs depends on the expression of viral receptors and coreceptors on the cell surface and by the viral use of host factors such as RNA binding motif protein 38 (RBM38) for the processing of its pre-mRNA during viral replication [61]. Variants in RBM38 gene have not been reported so far.…”
Section: Parvovirus B19 and Myocarditis: Genetic Studies Unravel Molementioning
confidence: 99%
“…The region of them shows a greater sequence variation in contrast to the large nonstructural protein(NS1) region that is highly conserved, which implies their function in host antivirus responses [28]. Expressions of the other two small nonstructural proteins of 11 kDa and 7.5 kDa were also documented [29,30], the former one was suggested as a potent inducer of apoptosis via enhancing viral DNA replication and virion release [31,32], while the function of 7.5 kDa protein is inconclusive.…”
Section: B19 Structurementioning
confidence: 99%